ChemPOV: Evaluating a digital game-based learning tool for organic chemistry through student-researcher collaboration (Journal of Applied Learning and Teaching, 2025)
In this study, we aim to investigate the application of game-based learning in organic chemistry education through the development and implementation of ChemPOV, a digital multiplayer board game. Uniquely, our team involved high school students collaborating with university researchers, providing insights into both the efficacy of the game and the value of engaging young students in chemical education research. Our team conducted trials with 176 junior high school students, divided into control and experimental groups. Data was collected through pre- and post-game surveys and quizzes. Results indicated correlations between student interest, engagement, and enjoyment in organic chemistry, with a minute improvement in academic performance for the experimental group. We also examined the benefits of applied learning experiences for the student researchers, who developed skills in research methodology, game design, and scientific communication. They participated in literature reviews, data analysis, and presented findings at international conferences. This research trial demonstrates the potential of involving young students in substantive research efforts and is a potential model for more inclusive approaches in STEM education.